Ascorbic acid from lyophilized camu-camu fruit: stability and quality control of hard capsules - Adele Salomão-Oliveira; Suely Souza Costa; Kátia Solange Cardoso Rodrigues dos Santos; Tatiane Pereira de Souza; Helyde Albuquerque Marinho (São Paulo State University (UNESP), 2016)
Camu-camu, a fruit found in the Amazon Basin river banks and lake shores, is known for its high ascorbic acid content together with, other antioxidants. This feature shows high potential for being exploited in agribusiness industry and pharmaceutical processes. However, its high acidity, as well as peel bitterness associated with the phenolic substances content, has discouraged its consumption while still fresh. The development of alternative forms for consuming this fruit, while still preserving its ascorbic acid and polyphenol content, in addition to its great potential for maintaining human health, has become a major economic activity in coastal communities. The present study evaluated the ascorbic acid stability found in camu-camu capsules. Lyophilization was performed with the fruit pulp and peel. Both freeze-dried fruitand powder-filled capsules were stored at 5° C. Ascorbic acid stability was monitored for 90 days using HPLC assay technique. The encapsulation process of freezedried pulp was considered satisfactory in the ascorbic acid conservation, since there was only a loss of 10% of its initial concentration throughout the study period for 60 days.